2017
DOI: 10.1038/srep40964
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis with a novel shear wave speed imaging for differential diagnosis of breast lesions

Abstract: To evaluate the diagnostic performance of a new two-dimensional shear wave speed (SWS) imaging (i.e. Toshiba shear wave elastography, T-SWE) in differential diagnosis of breast lesions. 225 pathologically confirmed breast lesions in 218 patients were subject to conventional ultrasound and T-SWE examinations. The mean, standard deviation and ratio of SWS values (m/s) and elastic modulus (KPa) on T-SWE were computed. Besides, the 2D elastic images were classified into four color patterns. The area under the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
(35 reference statements)
1
27
0
Order By: Relevance
“…The ICC values for SWE were higher than those for SE in our study. Our findings were comparable with the literature, since the reliability of SE features mostly depends on the experience of radiologists, whereas SWE has less operator dependency . Nevertheless, we found poor to good interobserver agreement for both SWE and SE.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The ICC values for SWE were higher than those for SE in our study. Our findings were comparable with the literature, since the reliability of SE features mostly depends on the experience of radiologists, whereas SWE has less operator dependency . Nevertheless, we found poor to good interobserver agreement for both SWE and SE.…”
Section: Discussionsupporting
confidence: 84%
“…The elastographic scale was set between 0 and 185 kPa. For the elastic modulus and SWV measurements, images that had smooth and parallel contour lines were used, where the accuracy of data was high . The uncolored region in the measurement box indicated that no shear wave was detected in this area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations